Lipid-free tuna muscle samples are suitable for total mercury analysis. (July 2021) - Médieu, Anaïs; Sardenne, Fany; Lorrain, Anne; Bodin, Nathalie; Pazart, Chloé; Le Delliou, Hervé; Point, David
Abstract: Tropical tunas are largely consumed worldwide, providing major nutritional benefits to humans, but also representing the main exposure to methylmercury, a potent neurotoxin that biomagnifies along food webs. The combination of ecological tracers (nitrogen and carbon stable isotopes, δ 15 N and δ 13 C) to mercury concentrations in tunas is scarce yet crucial to better characterize the influence of tuna foraging ecology on mercury exposure and bioaccumulation. Given the difficulties to get modern and historical tuna samples, analyses have to be done on available and unique samples. However, δ 13 C values are often analysed on lipid-free samples to avoid bias related to lipid content. While lipid extraction with non-polar solvents is known to have no effect on δ 15 N values, its impact on mercury concentrations is still unclear. We used white muscle tissues of three tropical tuna species to evaluate the efficiency and repeatability of different lipid extraction protocols commonly used in δ 13 C and δ 15 N analysis. Dichloromethane was more efficient than cyclohexane in extracting lipids in tuna muscle, while the automated method appeared more efficient but as repeatable as the manual method. Lipid extraction with dichloromethane had no effect on mercury concentrations. This may result from i) the affinity of methylmercury to proteins in tuna flesh, ii) the low lipid content in tropical tuna muscle samples, and iii) the non-polar nature of dichloromethane. Our study suggests that lipid-free samples, usually prepared for tropical tuna foraging ecology research, can be used equivalently to bulk samples to document in parallel mercury concentrations at a global scale. Graphical abstract: Image 1 Highlights: Scarcity of tuna samples makes essential to get the most out of a single sample. Dichloromethane is more efficient than cyclohexane to extract lipids. Dichloromethane extraction has no effect on Hg levels. Bulk and lipid-free tropical tuna samples can be used jointly to infer Hg levels.